(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Context Based errors are those errors which are wrongly used in sentences, though it seems valid. These errors would turn sentences into meaningless, which in turned to invalid documents. These words would not rectify in context or would do an automatic spelling checking. This paper explores the idea of Document Semantic called Latent Semantic analysis which can correct the context from this minor difference. This paper also reflects the importance of using this terminology. Keywords: stop word removal; stemming; term-frequency; singular value decomposition; cosine similarity.